The Food System in Portuguese urban planning: PROT-AML and challenges towards a necessary sustainable transition - Marat-Mendes, T.; Borges, J.C.; Pereira, M.; Lopes, S. (Seminário Internacional sobre Ambiente e Sociedade: Desafios atuais e trajetórias de mudança, 2020)
A request for a sustainable transition of urban planning and public policies has been urged by international and national Agendas, such as the UN2030 Urban Agenda, to mitigate the negative role of cities in Climate Change. An ongoing project SPLACH – Spatial Planning for Change aims to contribute to such a call through the design of good practices compendium to improve urban planning and decrease carbon emissions. Focusing on the Lisbon Metropolitan Area (LMA), SPLACH has highlighted the role of the food system to improve current planning practices and promote sustainable transitions. To do so, SPLACH has evaluated the integration of the food system in LMA planning instruments, namely at the municipal scale, concluding that integration is not yet achieved. But does regional planning counteract the frailties observed at the municipal scale in the LMA? This presentation aims to introduce the first results of an ongoing evaluation of the food system integration within the Regional Spatial Plan of LMA (PROT-AML). The PROT-AML acknowledgement of the diversity of agricultural practices within the regional territory exposes possibilities and niches that may help to enhance the food system into a future new PROT. A new regional plan should have emerged in 2012, when the 2002 PROT-AML was supposed to finish its implementation. By analyzing the key policies and the territorial model of the PROT-AML, this presentation reveals how the food system may contribute to improve further regional strategies towards a sustainable transition of our cities and territories.